Struktur Cerita Detektif Novel Manatsu no Houteishiki - Putri, Tiara Rosmika; Anwar, Fithyani (Departemen Sastra Jepang, Fakultas Ilmu Budaya, Universitas Hasanuddin, 2026)
This study examines the application of the classical detective formula in Keigo Higashino’s Manatsu no Hōteishiki through John G. Cawelti’s theoretical framework. The research aims to analyze how the five structural elements of detective fiction—introduction of the detective, crime and clues, investigation, the announcement and explanation of the solution, and ending are organized and modified in the novel. A descriptive qualitative method is employed through close reading and note-taking, with data sourced from narrative passages and dialogues in both the Japanese text and its Indonesian translation. The findings show that while the novel follows the classical detective formula, it introduces significant variations. The detective figure appears indirectly through Yukawa Manabu’s scientific reasoning. The central crime is initially disguised as an accident, supported by ambiguous clues that both guide and mislead characters and readers. The investigation progresses through unofficial channels, emphasizing scientific observation and interpersonal subtlety. The stages of announcing and explaining the solution unfold gradually and carry emotional weight, leading to an ending that highlights reconciliation rather than legal resolution. Overall, the novel reflects Higashino’s innovative adaptation of the detective formula and contributes to the development of modern Japanese detective fiction.